Constitutionality of constitutional settlement of disputes for the election of local heads - Ahmad Siboy (Faculty of Law, University of Merdeka Malang, 2022)
The authority to adjudicate disputes over the results of regional head elections continues to experience a shift in the judiciary. The delegation of authority to judge to the courts caused a polemic when the Pilkada was returned to the electoral regime, considering that the handover of auto power he the Special Courts Agency was based on the Constitutional Court's decision that the Regional Head Elections was a not General Election regime but the Regional Head Election regime. The purpose of this study is to describe the dynamics and the basis for the constitutionality of the authority to try it. The survey results stated that the judiciary's regulation on the settlement of ciary experienced three shifts, namely from the Supreme Court, the Constitutional Court, and the Special Courts Agency. However, the Special Courts Agency payment is unconstitutional because it is not a judicial institution that is explicitly and directly by the Constitution. The compensation of the amount by the Agency must be concretely normalized in the Republic of Indonesia Constitution so that the settlement process no longer moves, especially when the Regional Head Election is again designed to be returned to the General Election regime.How to cite item:Â Siboy, A. (2022). Constitutionality of constitutional settlement of disputes for the election of local heads.Â Jurnal Cakrawala Hukum, 13(2), 117-127. DOI:https://doi.org/10.26905/idjch.v13i2.6457.